2016
DOI: 10.5194/acp-16-12961-2016
|View full text |Cite
|
Sign up to set email alerts
|

Observations and regional modeling of aerosol optical properties, speciation and size distribution over Northern Africa and western Europe

Abstract: Abstract. The aerosol speciation and size distribution is modeled during the summer 2013 and over a large area encompassing Africa, Mediterranean and western Europe. The modeled aerosol is compared to available measurements such as the AERONET aerosol optical depth (AOD) and aerosol size distribution (ASD) and the EMEP network for surface concentrations of particulate matter PM 2.5 , PM 10 and inorganic species (nitrate, sulfate and ammonium). The main goal of this study is to quantify the model ability to rea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 49 publications
(41 reference statements)
2
22
0
Order By: Relevance
“…The AOD due to mineral dust is mostly underestimated and many factors may explain this. As already discussed in Menut et al (2016), the modelled size distribution may be inaccurate, while it is very sensitive for the AOD estimation. It was also shown that a bias in AOD calculation may exist but is not necessarily related to erroneous modelled surface concentrations of particulate matter (PM).…”
Section: Aod Chimere Vs Modismentioning
confidence: 99%
See 1 more Smart Citation
“…The AOD due to mineral dust is mostly underestimated and many factors may explain this. As already discussed in Menut et al (2016), the modelled size distribution may be inaccurate, while it is very sensitive for the AOD estimation. It was also shown that a bias in AOD calculation may exist but is not necessarily related to erroneous modelled surface concentrations of particulate matter (PM).…”
Section: Aod Chimere Vs Modismentioning
confidence: 99%
“…The modelled AOD is calculated by FastJX for several wavelengths over the whole atmospheric column, as detailed in Menut et al (2016). At the boundaries of the domain, climatologies from global model simulations are used.…”
Section: A2 the Chimere Chemistry-transport Modelmentioning
confidence: 99%
“…Their life cycle is fully represented with emission, transport, chemistry and deposition (wet and dry). Menut et al (2016) have detailed and analyzed aerosol speciation and size distribution in the CHIMERE model during the summer 2013 over Europe and Africa using the AERONET network for aerosol optical depth (AOD) and EMEP network for PM concentrations. For the AOD calculation, the aerosol optical scheme in the CHIMERE model considers mixed aerosols following the "core-shell" hypothesis detailed in Péré et al (2009) and evaluated in Péré et al (2010).…”
Section: Chemistry Transport With the Chimere Modelmentioning
confidence: 99%
“…The temporal correlation is much better for 2013 than for other years. This is probably due to a size distribution that is not necessarily well simulated from one day to another (shown by AOD and explained in Menut et al, 2016) but the relative contributions of fine and coarse aerosol atmospheric load are fairly reproduced. This feature highlights the high sensitivity of the AOD calculation to the modeled aerosol size distribution, although the overall mass emitted and transported is realistic.…”
Section: Optical Propertiesmentioning
confidence: 93%